Clinical Patterns and Frequency of Dermatological Manifestations Associated with Pregnancy - Hina Imtiaz, Saima Ilyas, Sadaf Sabir, Mehwish Khan, Filza Khalid, Eraj Mehreen Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Pregnancy is a physiological state of women which is associated with intricate endocrinological, immunological, metabolic & vascular changes. So pregnancy makes a woman susceptible to various changes in skin & appendages. Alteration to the immune state of the pregnant women is necessary to allow mother to tolerate genetically different tissue during pregnancy. Decrease in cell mediated immunity in normal pregnancy is mainly responsible for the higher frequency and severity of certain infectious diseases. Some of which can also be transmitted to the baby during child birth. Moreover there are marked changes in the levels of sex hormones particularly oestrogen & progesterone and this can lead to profound changes in skin. Objective: To find the prevalence of dermatological manifestations in pregnant patients presenting in a tertiary care hospital Study Design: Descriptive/Cross-sectional Study Setting: The study was done in the Dermatology unit DHQ Hospital Faisalabad. Duration of Study: The study was carried out from 1st October 2016 to 10th March 2017 Subjects and methods: 185 pregnant women presenting at any gestational age in dermatology department and patients referred from Gynae department with dermatological complaints were included in the study. Patients with pre-existing medical conditions such as hypertension and diabetes were excluded. Complete history and clinical features of the patients were accessed and relevant investigations were done to support the diagnosis. Final diagnosis was made on basis of history, clinical examination and laboratory confirmation of disease as per operational definition. LFT’s for intrahepatic cholestasis of pregnancy was done from DHQ laboratory and sample for skin biopsy for pemphigoid gestationis were sent to pathology laboratory FMU. All the data was recorded in a well-structured questionnaire. Results: Age range in this study was from 18 to 40 years with mean age of 30.129±3.26 years and mean duration of disease was 5.864±1.79 week. Majority of the women were with 2nd trimester of pregnancy (67%). 60% of women had no occupation. Striae Gravidarum was seen in 48.1%, Linea Nigra 45.9%, Melasma 25.4%, Hirsutism 16.2%, Palmer Erythema 8.1%, Atopic eruption of Pregnancy 11.9%, Polymorphic eruption of Pregnancy 3.2%, Intrahepatic Cholestasis of Pregnancy 1.6%, Pemphigoid gestationis 1.1%, Acne Vulgaris 9.7%, Vulvovaginal candidosis 8.1%, Urticaria 6.5% and Scabies was 5.4%. Practical Implication: We set out to investigate the prevalence of dermatological manifestations during pregnancy, as well as other clinical characteristics affecting pregnant women in Pakistan. Conclusion: If infections during pregnancy are diagnosed at the earliest stage it may prevent morbidity during and after antenatal period. Keywords: Pregnancy; Dermatological manifestations; Frequency, Clinical Patterns, Pemphigoid Gestationis, Acne Vulgaris, Vulvovaginal Candidosis,